Healthcare service network analysis: Northern region’s healthcare service network of cleft lip and cleft palate - Supaksiri Suwiwattana (2020)
© 2020, King Mongkut's Institute of Technology Ladkrabang. All rights reserved. This research focused on the analysis of healthcare network of cleft lip and cleft palate patients at Chiang Mai University Craniofacial One Stop Service Center as the treatment hub for the northern part of Thailand. The delay was founded during the treatment plan. Patient classification was carried out using K-mean technique. The results from the classification show that the best case patient is the case with the average distance to the treatment center (64.20 km) without complication symptoms. To improve the service of this network, the proposed solution is to increase the number of treatment centers. Two hospitals, Fang and Chomthong hospitals, were proposed as the potential hospitals in this network. The mathematical model was proposed for patient assignment. Twelve districts were assigned to Maharaj Nakorn Chiang Mai hospital and 6 districts were assigned to Fang hospital and Chomthong hospital. The average distances of three groups were 32.84, 55.55 and 62.28 km less than the best case distance at 64.20 km. When the real implementation is considered, both hospitals have to increase their capabilities by hiring more specialist for this service that incurs 2.64 million baht/year for Fang hospital and 2.16 million baht/year for Chomthong hospital. With the proposed solutions, the critical time of the treatment plan can be reduced from 2,663.6 to 2,504.5 days that was 5.97%.